Improving the Ability and Motivation of School Librarians and Teachers Using the SliMS Application Through in-House Training at SD Negeri Tukharjo Samigaluh Kulon Progo for the 2021/2022 Academic Year - Redemtus Hertanto (Universitas Islam Indonesia, 2022)
This study aims to increase the motivation and ability of school librarians and teachers in managing school libraries using the SLiMS application, through In House Training at SD Negeri Tukharjo Kapenewon Samigaluh, Kulon Progo Regency, Special Region of Yogyakarta. This research is a School Action Research using the In House Training method which is carried out in 2 cycles, each cycle consisting of 2 meetings. The technique of collecting data in this study was carried out using observation and documentation. The results of this study are an increase in motivation and the ability of participants (librarian staff and teachers) in managing the library by using the SLiMS application program. The results based on the acquisition of the total ability score of IHT participants in Cycle I 1st and 2nd meetings there is an increase of 4.33; while in the second cycle of the 1st and 2nd meetings, the total score obtained was an increase of 4.50; while based on the percentage of the first and second meeting cycles; there was an increase of 5.78%; as for the second cycle of the 1st and 2nd meetings there was an increase of 6.00%; while based on the motivation of the participants obtained; the total score of the first cycle of the 1st meeting reached 33.5, the second meeting reached 39.00 there was an increase of 5.65; then the second cycle of the 1st meeting the total score reached 44.00; the second meeting reached 46.33; there was an increase of 2.33; The following is based on the percentage of the first cycle of the 1st meeting reaching 67.00%; while the average number of the 2nd meeting reached 78.00%, there was an increase of 11.00%; while in the second cycle of the 1st meeting the average score based on percentage reached 88.00%; while at the second meeting it reached 92.67; there is an increase of 4.67%; while based on the ability of researchers; the results of the observation in Cycle I, the 1st meeting, the ability of researchers to manage IHT activities, the average score reached 2.61; based on percentage reached 65.30%; the 2nd meeting reached 3.3; the following based on the percentage reached 82.52%; Furthermore, the second cycle of the 1st meeting the average score reached 3.51; based on percentage reached 87.65; following the 2nd meeting it reached 3.81, while the average number of percentages reached 95.17%,